Did Program Support for the Poorest Areas Work? Evidence from Rural Vietnam - Hai-Anh H. Dang; Klaus Deininger; Cuong Viet Nguyen (Global Labor Organization (GLO), 2024)
We investigate the impact of a large-scale poverty alleviation program targeted at 62 poorest districts in Vietnam, analyzing multiple datasets spanning the past 20 years with a regression discontinuity design with district fixed effects. While we do not find significant program effects on household welfare (as measured by per capita income and poverty) and local economic development (as measured by nighttime light intensity and establishment of new firms), we find that the program facilitates a shift from farm to nonfarm employment and significantly increases the share of nonfarm income for rural households. One possible explanation for the positive effects on nonfarm employment is the improved access to credit that the program provides to participating households. We also find that the program increases household access to electricity, public transfer, educational subsidies for students residing in the program districts, and healthcare utilization, possibly through improving availability of commune healthcare centers.
Keywords: C15; D31; I31; O10; O57; 330; poverty; targeting; household surveys; Vietnam